Application of Definite Indices For Assessment of Some Heavy Metals Pollutants in surrounding Soils of Metal Recycling Companies in Sulaimani Governorate - Hama-Karim, Biza Mohammed; Majid, Salih Najib (Sulaimani Journal for Pure and Applied Sciences, 2020)
This study was conducted to apply some indices assessment methods for heavy metal pollution in the soil as well as to study the variation in physicochemical characteristics of the soil samples taken from different sites around scrap metal recycling companies in the township of Bazian behind Bibijak village, Sulaimani Governorate. Physicochemical parameters results indicated relatively high variation along with the ranges of the specified distances from the companies, directions, and depths as well as between the companies even though the two companies are adjacent to each other. Additionally, correlation analysis approved the significant effect (at p ≤ 0.05) of some soil physicochemical properties on the concentrations of the investigated heavy metals in the studied soils. In general, the concentration of all the investigated metals were mostly higher in surface soils (D1) samples rather than the subsoil (D2) samples at all the distances ranges and directions of the sampling sites. The spatial occurrence of the studied metals followed the order of; Fe > Mn > Ni > Cr > V > Co, and this may be in a sequence that agrees with the trend of main scrap metals components. Results of the simple Geoaccumulation index (Igeo) for Fe, Co, Cr, Mn, Ni, and V indicated that the soil qualities were generally in unpolluted status, but limited sampling sites fell in class one which characterized by uncontaminated to moderately polluted. On the contrary, the comparative integrated pollution load indices (PLI) and Nemerow Pollution Index (PINemerow) showed that most of the studied sampling sites around the scrap metal recycling companies were slightly polluted according to PLI, but they were in warning limit (precaution domain) according to PINemerow in consequence of the industrial activity of Sulaimani Steel and Super Steel at all the four main directions, and all distances ranges.
Keywords: Physicochemical parameters; Heavy metals; Pollution Indices; Scrap recycling companies; Soil; SulaimaniGovernorate